Intraosseous endoscopic-assisted lesion debridement combined with free fibular vascularized transplantation for non-traumatic femoral head necrosis: A comparative study with core decompression - Yalong Yang; Zhao Zhang; Yuanyuan Wei; Yang Li; Junliang Liu; Bo Wang; Shouhu Mi; Jintong Liu; Yongqiang Zhang; Yongming Guo; Meng Wu (Journal of Orthopaedic Surgery)
Background Non-traumatic femoral head necrosis results from insufficient blood supply to the femoral head, causing hip pain, restricted movement, and eventual collapse. This study compares the efficacy of endoscopy-assisted lesion debridement with free vascularized fibular grafting versus core decompression (CD) to identify a more effective surgical approach for treating osteonecrosis of the femoral head (ONFH). Methods This retrospective study included 83 patients with femoral head necrosis who were treated between January 2010 and December 2020. The patients were divided into Group A (intraosseous endoscopic-assisted lesion debridement combined with free fibular grafting, n = 45) and Group B (CD, n = 38) based on their treatment approach. Preoperative general data, intraoperative variables such as operation time and blood loss, and postoperative assessments of Harris Hip Score, Visual Analog Scale (VAS), as well as imaging evaluations through X-ray and MRI for femoral head shape restoration and healing, were conducted at 1 week, 4 weeks, 3 months, 6 months, and 12 months post-surgery. Results A follow-up of more than 2 years was conducted for both groups of patients. Preoperative general data, such as age, showed no significant difference between the two groups ( p > 0.05). Group A patients had significantly better Harris Hip Scores at 3, 6, and 12 months postoperatively, as well as significantly lower VAS scores at 4 weeks, 3 months, 6 months, and 12 months post-surgery compared to Group B ( p < 0.05). In Group A, 3 patients experienced elevated body temperature (maximum 38.6°C), which was considered to be postoperative absorption heat; their temperatures returned to normal within 2–3 days following symptomatic treatment. All surgical incisions in both groups healed well, with no vascular or nerve injuries or other related complications. Additionally, imaging results showed that 4 hips in Group A developed femoral head collapse, compared to 10 hips in Group B. In Group A, 4 patients (4/45, 8.9%) with collapse were in ARCO stage II, while in Group B, 6 patients (6/38, 15.7%) were in ARCO stage I and 4 patients (4/38, 10.5%) were in ARCO stage II. Overall, Group A had a non-collapse rate of 91.1% (41/45) in early-stage femoral head necrosis, which was significantly higher than Group B’s 73.7% (28/38) ( p < 0.05). Conclusion Intraosseous Endoscopic-assisted lesion debridement combined with free fibular grafting shows superior clinical efficacy compared to CD in the treatment of femoral head necrosis. It effectively improves femoral head morphology, alleviates pain, restores joint function, and has a lower complication rate, making it a promising approach for further clinical application and promotion.